TRG/Western Kentucky University: All University Collaboration Model - Burch, Barbara; Evans, Sam; Lee, David (Educational (Re)naissance, 2013)
As an institution built on the foundation of a Normal School, collaboration among faculty members and across program areas and academic units have been part of Western Kentucky University’s (WKU) heritage since 1906. In addition to the various collaborative initiatives across campus, there are a variety of initiatives that involve various agencies across the community, including ongoing partnerships with local and area school districts, P-16 Councils, and the Green River Region Educational Cooperative. These collaborations have been enhanced, especially since the court decision resulting in Kentucky’s Educational Reform Act (KERA) in 1990 (Rose v. Council, 1989). In the early 1990s the College of Education and Behavioral Sciences created the Task Force on Education Reform – High Schools and the Task Force on Research-Based Instructional Strategies to facilitate institutional work relative to KERA. Both Task Forces involved faculty from what is now the Ogden College of Science and Engineering and the Potter College of Arts and Letters.